PENCITRAAN DENGAN REFLEKSI GELOMBANG ULTRASONIK UNTUK OBJEK SILINDER - Joko Sarwono, R.Sugeng
Tomography is a method for reconstructing image of an object from its projections. In the strict sense of the word, a projection at a given angle is the integral of the image in the direction specified by that angle. Computerized reflection tomography is basically an outgrowth of ultrasonic transmission tomography aimed at providing quantitative images displaying a specific parameter of tissue. Reflection tomography images the ultrasonic reflectivity, while transmission tomography images the velocity or attenuation in the medium. An ultrasonic scanner system for data acquisition process of ultrasonic reflection tomography has been built. The system consists of a plexyglass tank with dimension of 50 x 40 x 40 cm filled with water, a plate on which the object placed, a step motor from RS Component RS 440-442 connected to the plate to rotate the object, H2N type of Ultrasonic Transducer-Receiver with 22 mm of diameter from Krauftkramer Branson with 2 Mhz centre frequency, and a pulse generator WDM from Krauftkramer Branson. The system is controlled by a Personal Computer Pentium 60 Mhz, with 24 Mbyte RAM. Data acquisition processes was conducted in DOS system, using 8 bit ADC card SC202 from BMC system, with 20 Mhz sampling rate. The measurement objects were three PVC cylinder with various inner form, immersed in water. The off line reconstruction result of the three objects using raw measurement data, half of reflection data (from the center to the nearest reflector from transducer), only the information of the peak value of every pulse echoes and its location, and only the information of the first signals of every pulse echoes and its location, shown that the objects were correctly images.